AN INVESTIGATION ON RESIDENTS’ SUPPORT OF TOURISM DEVELOPMENT IN PENANG, MALAYSIA - Chia-Sin Loh; Yen-Nee Goh; Salmi Mohd Isa; Mao-Seng Ting; Ghazanfar Ali Abbasi (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This study demonstrates the adaptation of Social Exchange Theory (SET) to examine the relationship between community attachment, community involvement, residents’ place image, perceived benefits, perceived costs, and residents’ support of Penang sustainable tourism development. A total of 196 data were collected face-to-face by a self-administered questionnaire to residents who live in George Town, Penang, Malaysia. A partial least squares (PLS) analysis was applied to assess the measurement model and the structural model. The proposed model showed useful predictive and explanatory power. Community involvement exhibited a significant effect on residents’ support of tourism development. Surprisingly, community attachment, residents’ place image, perceived benefits, and perceived cost were found to be insignificant to residents’ support. There is a positive relationship between community attachment and residents’ place image with perceived benefits and perceived costs. On the contrary, the influence of community involvement towards perceived benefits and perceived costs were not supported. The findings of this study provide a better understanding of the factors that influence residents’ support on sustainable tourism development in Penang, Malaysia. Additionally, this study also provides insightful implications to regulatory bodies, owners of tourism businesses, and property developers.